The impact of modified modular health teaching on enhancing the client's cognitive level on diabetes mellitus and compliance to diet and medication regimen - Maghuyop, Samuel; Torres, Melanie Joy.; Ampongan, Antonnette Jennifer; Benemerito, Rommel .; Cabela, Joy Caromel; Francisco, Jr., Francisco; Oropesa, Ruth .; Pagulayan, Divina Gracia .; Patawaran, Kristine Grace; Regala, Trina Fe.; Verzo, Cristina (Manila College of Nursing University of the Philippines Manila, 1994)
The self-care capabilities of a diabetes mellitus patient is vital in the effective control of the illness. This is usually developed according to the knowledge and training imparted by health personnel to the patient. Thus this study was done to determine the following: (1) the presence of a relationship between health teaching and the patient’s cognitive level. and compliance to diet and medication regimen; (2) the effect of health teaching on the patient’s cognition on illness and its management and his or her’ actual compliance to diet and medication regimen; (3) the factors affecting an individual's improvement of cognitive level and compliance to diet and medication regimen.

The study showed a significant relationship of health teaching and cognitive level as influenced by some factors based on the data gathered, the respondents” cognitive level increased as shown by a more significant increase in scores of respondents given health teaching. However, patients' compliance did not show a relationship with the presence of health teaching. One variable was seen to have much influence on the increase in cognitive level and this is the education level.

Therefore, the study has proven a presence of a relationship between health teaching and cognitive level as contrary to compliance. Also, patients with high educational attainment showed better understanding of health teaching as shown by increase in score.
Research (In partial fulfillment of the requirements in the course N199: Nursing Research) -- University of the Philippines Manila, April 1994.
Keywords: Nursing -- Research